Initiation of breast-feeding practice and associated factors among mothers who have infants less than 12 months of age in Debre Tabor Town, North West Ethiopia, 2021: A multicenter community-based cross-sectional study. Issue 4 (August 2022) - Feleke, Dejen Getaneh; Chanie, Ermias Sisay; Yimam, Aster Melaku; Tassaw, Sheganew Fetene; Alemu, Kassaw Demilie; Wassie, Fentahun Dires; Eyayu, Dawit; Gietaneh, Wodaje; Boled, Abebe Tiruneh; Alemayehu, Tikuneh Yetneberk; Dagnaw, Eyaya Habtie; Tsegaye, Gebiyaw Wudie; et al.
Abstract: Introduction: initiation of breastfeeding is crucial in preventing newborn deaths and influences childhood nutrition. There was limited updated evidence regarding early initiation of breast-feeding practice and associated factors among the target population in the study area. Objective: To assess initiation of breastfeeding practice and its associated factors among mothers who have infants less than six months of age in, North West Ethiopia, 2020. Methods: The Community based quantitative cross-sectional study was conducted among 405 respondents in the stud area, then data would be entered and analyzed by using SPSS version 20 statistical packages. Bivariate and multivariable logistic regression model analysis would be done. Odds ratio with 95% confidence was computed to determine the level of significance-value less than 0.05 considered as significant. Result: This study showed that 94.7% of mothers in Debre Tabor Town practiced initiation of breastfeeding for their infants within the Less Than 12 Months of age. In multivariable analysis I n f a n t S e x, Female [AOR (95% CI) = 0.068 (0.002, 1.659), and Age of Mother 20–24 years [AOR (95% CI) = 2.33 (0.030, 17.12)], 25–29 years ((AOR = 8.20 [(95% CI: 12.212, 22.189]), and 30–34 years (AOR = 4.48 [95% CI: 0.463, 15.478], Assists (Attend) during delivery, Doctor (AOR = 0.644 [95% CI: 0.041, 10.138]) and Encourage BF by religious father (AOR = 6.669 [(95% CI: 4.27, 8.895]) were remained significantly associated with the outcome variable with at 95% CI and P- value of <0.05. Conclusion: and Recommendation: The prevalence of EIBF among mother-infant pairs of less than 12 months in debre tabor town, Northwest, Ethiopia, was found to be high as compared to national and global infant and young child feeding guidelines. However; it shows improvement as compared with some previous studies in Ethiopia. I n f a n t s e x, age of mother, assists during delivery, and encourage BF by religious father were factors associated with outcome in the stud area.